SIMULATING CIRCULATION NATURE AROUND BACH LONG VI ISLAND BY A MATHEMMATICAL MODEL - An, Pham Hai; Tu, Tran Anh (Vietnam Journal of Marine Science and Technology, 2014)
Bach Long Vi is the furthest offshore island in the Tonkin gulf. As one of the frontier islands, the information about the hydrodynamic factors such as wave, current, tide is especially needed for scientific researches as well as designing protection engineering. Due to the limitation of hydrodynamic observation data in this area, the use of mathematical models to simulate hydrodynamic regime is a good way to understand about circulation around the island. By using the nesting techniques in Delft3D model, the circulation around Bach Long Vi island was simulated, from that the picture of circulation in this area is clear because of the influence of tidal and wind surface. The initial simulation results show that the circulation of offshore area has been controlled by the circulation of the Gulf of Tonkin, the flow has two main directions, including east-northeast and west-southwest. Meanwhile, the coastal island has the appearance of the local cyclone and anticyclone as well.